The Book of Clear Arabic Expression regarding the Arab Tribes of Egypt : An edition, translation and study of al-Maqrīzī's al-Bayān wa'l-iʿrāb ʿammā bi-arḍ Miṣr min al-aʿrāb - Daaïf, Lahcen; Rapoport, Yossef (Bibliotheca Maqriziana, 2024)
Al-BayÄn wa'l-iÊ¿rÄb Ê¿ammÄ fÄ« ará¸ Miá¹£r min al-aÊ¿rÄb is an influential treatise on the Arab and Berber groups that inhabited the Egyptian countryside in the late medieval period. The work brings together al-MaqrÄ«zÄ«'s life-long preoccupation with the history of Egypt and his parallel interest in the history of the Arabs, pitting the lineage-based ideology of Arab rebels against the Mamluk elite of manumitted slaves. Over the past century, the BayÄn has been repeatedly deployed in public debates about the Arab identity of Egypt. This book offers a critical study of the treatise in its fifteenth century context, an academic edition, and a first translation into English.